GLOBAL PERSPECTIVE OF SCIENCE MATERIALS AND ENGINEERING - Palomino-Infante, A. (1999)
We can say that the science and engineering of materials as such, arises in the heat of the big projects Aerospace and Defense, which has had as contenders to the United States and the former USSR in the years of the Cold War. However, we know that historically the discovery and use of materials by man, has drawn almost inexorably the course of their own development. No wonder, therefore, that this science is largely responsible for the great technological advances that humanity is experiencing at the present time.